Surface Properties of p‐GaN and Formation of Nickel Metal Contacts - Miettinen, Mikko; Nuutila, Vesa; Jahanshah Rad, Zahra; Ebrahimzadeh, Masoud; Ruokonen, Anni; Punkkinen, Risto; Lehtio, Juha-Pekka; Punkkinen, Marko; Laukkanen, Pekka; Kokko, Kalevi; Suihkonen, Sami; Savin, Hele; et al. (Wiley, 2025)
Nickel (Ni) is the key component in ohmic contacts for Mg-doped p-GaN, but the detailed formation mechanisms of the ohmic contact have not yet been understood. In this work, the effect of potassium hydroxide (KOH)-based chemical treatment on the surface of p-GaN is investigated using X-ray photoelectron spectroscopy (XPS), scanning tunneling microscopy (STM), and low-energy electron diffraction (LEED). Ni metal contacts on the chemically treated p-GaN surface are studied using transfer length method (TLM) and synchrotron radiation photoelectron spectroscopy (SR-XPS). The chemical treatment of p-GaN improves the brightness of the (1x1) hexagonal diffraction pattern in LEED and keeps the 2D terrace structure in STM visible. Concomitantly, XPS shows that the amount of O, C, and Mg-O bonds at the surface were reduced. Ni/p-GaN provided an ohmic contact after annealing in ultra-high vacuum (UHV) at 500 degrees C. Simultaneously, SR-XPS shows the diffusion of Ga to Ni and the formation of a previously unreported Ga 3d component, which has a surprisingly narrow line shape, indicating that it originates from a crystalline interface phase. Diffusion of Ga is discussed to cause Ga vacancies and acceptor levels in the bandgap increasing carrier tunneling, thus enabling ohmic contact.